2019
DOI: 10.1105/tpc.19.00003
|View full text |Cite
|
Sign up to set email alerts
|

RST1 Is a FREE1 Suppressor That Negatively Regulates Vacuolar Trafficking in Arabidopsis

Abstract: FYVE domain protein required for endosomal sorting1 (FREE1), a plant-specific endosomal sorting complex required for transport-I component, is essential for the biogenesis of multivesicular bodies (MVBs), vacuolar degradation of membrane protein, cargo vacuolar sorting, autophagic degradation, and vacuole biogenesis in Arabidopsis (Arabidopsis thaliana). Here, we report the characterization of RESURRECTION1 (RST1) as a suppressor of free1 that, when mutated as a null mutant, restores the normal MVB and vacuole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 56 publications
(81 reference statements)
0
10
0
Order By: Relevance
“…Interestingly, plants have evolved unique ESCRT components to regulate ESCRT-mediated processes, such as the VPS4/SKD1 ATPase positive regulator POSITIVE REGULATOR OF SKD1 (PROS), the TOM1-LIKE (TOL) family proteins, and the ESCRT-0 function like protein FYVE DOMAIN PROTEIN REQUIRED FOR ENDOSOMAL SORTING 1 (FREE1) in Arabidopsis (Korbei et al, 2013;Gao et al, 2014;Reyes et al, 2014). Moreover, using genetic suppressor screening of FREE1 mutant, a plant-specific BRO1-DOMAIN PROTEIN AS FREE1 SUPPRESSOR (BRAF) and the RESURRECTION1 (RST1) have been identified recently (Shen et al, 2018;Zhao et al, 2019). BRAF may function as a negative regulator of ESCRT in plant.…”
Section: Pvc/mvb Biogenesis and Maturationmentioning
confidence: 99%
“…Interestingly, plants have evolved unique ESCRT components to regulate ESCRT-mediated processes, such as the VPS4/SKD1 ATPase positive regulator POSITIVE REGULATOR OF SKD1 (PROS), the TOM1-LIKE (TOL) family proteins, and the ESCRT-0 function like protein FYVE DOMAIN PROTEIN REQUIRED FOR ENDOSOMAL SORTING 1 (FREE1) in Arabidopsis (Korbei et al, 2013;Gao et al, 2014;Reyes et al, 2014). Moreover, using genetic suppressor screening of FREE1 mutant, a plant-specific BRO1-DOMAIN PROTEIN AS FREE1 SUPPRESSOR (BRAF) and the RESURRECTION1 (RST1) have been identified recently (Shen et al, 2018;Zhao et al, 2019). BRAF may function as a negative regulator of ESCRT in plant.…”
Section: Pvc/mvb Biogenesis and Maturationmentioning
confidence: 99%
“…Further studies revealed that BRAF competes with FREE1 for binding to Vps23A on MVB and thus compromises FREE1 function in MVB biogenesis and MVB-mediated membrane protein sorting to the vacuole (Shen et al 2018). However, RST1 exerts an opposite effect on the vacuolar trafficking of FREE1, and monitors the gene expression of the putative plant ESCRT-0 member TOM1-like protein 4 (TOL4) through an unknown mechanism (Zhao et al 2019). Although the basic endosomal functions of the plant ESCRT machinery have been characterized and some potential regulators of FREE1 function have been identified, the mechanisms that regulate constitutive ESCRT activity, such as the turnover of ESCRT components or the spatio-temporal regulation of ESCRT activity at the level of gene expression, are poorly understood.…”
Section: Introductionmentioning
confidence: 99%
“…We speculate that the increase level of RST1 might function as a compensation mechanism for the overall accelerated protein synthesis in pdk1.1 pdk1.2. Moreover, RST1 was recently identified as a regulator of the vacuolar protein degradation pathway (61), implying a role of PDK1 in the endomembrane trafficking process. Interestingly, precursors of two major storage proteins, 2S albumin and 12S globulin (63, 64) (Table 1) are significantly It is noteworthy that the pdk1.1 pdk1.2 phenotype is not fully rescued by pel1 mutations, or by a truncated PDK1.1N transgene.…”
Section: Discussionmentioning
confidence: 99%
“…pdk1.2 exhibits pleotropic growth and developmental defects, including significantly reduced fertility, which may be due to the changed levels of embryonic development-related proteins EMB 1923, RESURRECTION1 (RST1)(32,(59)(60)(61) and YELLOW STRIPE-LIKE3 (YSL3)(62). Notably, RST1 is a crucial regulator for RNA metabolism and thus the post-transcriptional gene silencing pathway(32,60).…”
mentioning
confidence: 99%